(untitled) (Jurnal Ilmiah Sains dan Teknologi, 2021)
Currently, a good entrance management is needed to make it easier for vehicle users to get comfort and security. Management of the gate system that is not good will cause a negative image in the eyes of users going in and out. One indicator of a good gateway system management is a smooth service process and good security. Good creation requires the support of all existing components. The gate facility is a computerized system that makes it easier for vehicle users and provides security. The gateway system using Radio Frequency Identification Digital (RFID) is able to provide both the things that users need safely and efficiently. The purpose of this final project is to realize a prototype entrance using RFID as an opener and access rights to enter and exit the parking lot. The technology used is RFID as a user ID identifier, Arduino Uno as the controller, and Microservo as the driver of the existing gate bars. The test is done by attaching the RFID card to the RFID reader. The test results show that the distance limit for RFID detected is 3 cm.